Measurement of muscle mass for diagnosing sarcopenia: Is it enough? - YILDIZ, YASİN; TUFAN ÇİNÇİN, ASLI (My University, 2024)
We read with interest the study by Kubrak et al. investigating the effect of muscle depletion on overall survival by calculating lumbar (L3) skeletal muscle index (SMI) in patients with head and neck cancer [1]. However there is terminology confusion in the article. The authors of the study determined the title of the study as "Quantifying the severity of sarcopenia in patients with cancer of the head and neck", but according to the new EWGSOP2 criteria, as this study investigates the effect of low muscle mass rather than sarcopenia. Sarcopenia is a progressive and generalised skeletal muscle disorder that can lead to adverse outcomes such as falls, fractures, physical disability and death. Although the 2010 EWGSOP [2] sarcopenia diagnosis was based on low muscle mass, the 2019 EWGSOP2 [3] sarcopenia diagnostic criteria have shown that muscle strength decline is more prominent and more successful in predicting adverse events. The EWGSOP2 uses muscle strength as the most reliable and main measurement parameter of muscle function. The use of grip strength and chair stand test is recommended for measuring muscle strength. Sarcopenia is probable when low muscle strength is detected and the diagnosis of sarcopenia is confirmed when possible sarcopenia is accompanied by low muscle mass, When low muscle strength, low muscle quantity/quality and low physical performance are all detected, sarcopenia is considered severe [3].
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Yoğun Bakım; Beslenme ve Dietetik; Tarımsal Bilimler; Ziraat; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Intensive Care; Nutrition and Dietetics; Agricultural Sciences; Agriculture; Health Sciences; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Tarım Bilimleri; Klinik Tıp; BESLENME VE DİYETETİK; YOĞUN BAKIM; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); AGRICULTURAL SCIENCES; CLINICAL MEDICINE; NUTRITION & DIETETICS; CRITICAL CARE MEDICINE; Beslenme ve Diyetetik; Yoğun Bakım Tıbbı; Critical Care and Intensive Care Medicine; Cancer; EWGSOP2; Head and neck; Sarcopenia